ROLE OF ASCORBIC ACID IN IMPROVING MOOD IN PATIENTS WITH DEPRESSION: A RANDOMIZED CONTROLLED TRIAL - Wadud, Shamaila; Fatima, Sadia; Irfan, Muhammad (Journal of Postgraduate Medical Institute, 2024)
Objective: To find out the effect of ascorbic acid in improving mood in patients undergoing treatment for depression. Methodology: A randomized control trial was conducted at Department of Psychiatry, Mercy Teaching Hospital, Peshawar, involving 102 subjects equally divided into two groups: interventional (IG) and control (CG). The IG received antidepressants (+ Psychological support) and daily Ascorbic Acid 500 mg, while the CG received antidepressants (+ Psychological support). Plasma ascorbic acid levels were carried out in addition to Hamilton Depression Rating Scale (HAM-D). Data analysis was performed using SPSS 26 and paired sample t test was used as the test of significance. This trial was registered at Australian New Zealand Clinical Trial Registry (ACTRN12624000525583). Results: The baseline HAM-D score for the overall sample was 21.81±6.16 and ascorbic acid level of 1.27±0.45, approaching the lower limit of the normal range. Following a three-month treatment, the mean HAM-D score was 13.39±7.39 (p=0.000), and ascorbic acid level of 1.97±0.69 (p=0.000). In the IG, baseline values were 20.92±6.49 for HAM-D and 1.32±0.48 for ascorbic acid, and the end-study values were 14.35±8.29 for HAM-D and 1.94±0.65 for ascorbic acid, with a significant p-value of 0.000. Similarly, at baseline, the HAM D-CG value was 23.14±5.68 and ascorbic acid value was 1.25±0.41, which was 12.53±6.46 for HAM-D and 1.99±0.74 for ascorbic acid at end-study, with a significant p-value of 0.000 for both. Conclusion: Combination of ascorbic acid and antidepressants (+ Psychological support) showed a similar level of effectiveness compared to the use of antidepressants (+ Psychological support).